Angle specificity of the knee extensor age-related profile in young female athletes - Rousanoglou, E. N.; Boudolos, K. D. (International Journal of Sports Medicine, 2008)
The angle specificity of the knee extensor age-related profile was examined in young females (13 - 19 yr). Twenty-one track & field jumpers, 20 volleyball players and 20 non-active females were separated into the youngest and the oldest age categories, based on the official competitive age categories. The maximum knee extensor isometric torque (TMAX) was measured at 9 knee angles. The relationships between TMAX at the peak of the torque-angle curve and at the other knee angles (angle-angle relationships) were expressed by R2 (%). Statistics included two-way ANOVA for age category differences and curve fitting to R2 joint angle trend lines. Differences between age categories were significant for the volleyball players and the non-active females (p < 0.05). Age category had an angle specific impact on angle-angle relationships in the athletes, with the youngest ones demonstrating greater R2 decrease at the more extended, or more flexed, knee angles. Significant quadratic R2 joint angle trend lines were found in all track & field jumpers (p < 0.05) and, in the youngest only volleyball players (p < 0.05), but not in the non-active females (p > 0.05). In conclusion, the knee extensor profiles of young female athletes show an age-related angle specificity that should be accounted for when treating athletes within the age range examined.